FIGURATIVE LANGUAGE IN MICHAEL BUBLE’S SELECTED SONG LYRICS - Hadisaputra, Andreas Avellino; Putri, I Gusti Ayu Vina Widiadnya; Juniartha, I Wayan (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This study analyzes the figurative language used in song lyrics of Michael Buble’s song lyrics. The song lyric was analyzed based on the theory proposed by Knickerbocker and Reninger (1963) to find out the types of figurative language in the song lyrics and the theory of meaning based on theory proposed by Leech (1981) to find out the meaning of each figurative language. The study aims to provide a better understanding of the figurative language types and the meaning of figurative language on Michael Buble’s song lyrics. This study used qualitative method to collect data. The types of figurative found in Michael Buble’s song consist of 11 types, they are simile, metaphor, personification synecdoche, metonymy, imagery, symbol, allusion, paradox, hyperbole, and irony. Meanwhile, the types of meanings of figurative language found were only 5 out of 7 types, they are conceptual meaning, connotative meaning, collocative meaning, affective meaning and thematic meaning